The role of protein glycosylation in the occurrence and outcome of acute ischemic stroke - Jianzhuang Li; Yanmei Qiu; Chunlin Zhang; Hailing Wang; Rentang Bi; Yanhao Wei; Yanan Li; Bo Hu (Elsevier, 2023)
Acute ischemic stroke (AIS) is a serious and life-threatening disease worldwide. Despite thrombolysis or endovascular thrombectomy, a sizeable fraction of patients with AIS have adverse clinical outcomes. In addition, existing secondary prevention strategies with antiplatelet and anticoagulant drugs therapy are not able to adequately decrease the risk of ischemic stroke recurrence. Thus, exploring novel mechanisms for doing so represents an urgent need for the prevention and treatment of AIS. Recent studies have discovered that protein glycosylation plays a critical role in the occurrence and outcome of AIS. As a common co- and post-translational modification, protein glycosylation participates in a wide variety of physiological and pathological processes by regulating the activity and function of proteins or enzymes. Protein glycosylation is involved in two causes of cerebral emboli in ischemic stroke: atherosclerosis and atrial fibrillation. Following ischemic stroke, the level of brain protein glycosylation becomes dynamically regulated, which significantly affects stroke outcome through influencing inflammatory response, excitotoxicity, neuronal apoptosis, and blood-brain barrier disruption. Drugs targeting glycosylation in the occurrence and progression of stroke may represent a novel therapeutic idea. In this review, we focus on possible perspectives about how glycosylation affects the occurrence and outcome of AIS. We then propose the potential of glycosylation as a therapeutic drug target and prognostic marker for AIS patients in the future.